2019
DOI: 10.1371/journal.pone.0215390
|View full text |Cite
|
Sign up to set email alerts
|

Tissue steroid levels in response to reduced testicular estrogen synthesis in the male pig, Sus scrofa

Abstract: Production of steroid hormones is complex and dependent upon steroidogenic enzymes, cofactors, receptors, and transporters expressed within a tissue. Collectively, these factors create an environment for tissue-specific steroid hormone profiles and potentially tissue-specific responses to drug administration. Our objective was to assess steroid production, including sulfated steroid metabolites in the boar testis, prostate, and liver following inhibition of aromatase, the enzyme that converts androgen precurso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The SRD5A2 in the prostate is key to the local conversion of testosterone to DHT, a particularly potent androgen involved in the maintenance of prostate function. Local activity of the SRD5A2 enzyme, coupled with local conversion of testosterone sulfate to testosterone [ 69 , 70 , 71 ], suggests local androgenic signaling independent of fluctuations in peripheral testosterone. The importance of SRD5A2 to prostatic development in humans and laboratory rodents is demonstrated by the small and undeveloped prostates present when a mutation in the gene prevents expression of a functional enzyme [ 14 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SRD5A2 in the prostate is key to the local conversion of testosterone to DHT, a particularly potent androgen involved in the maintenance of prostate function. Local activity of the SRD5A2 enzyme, coupled with local conversion of testosterone sulfate to testosterone [ 69 , 70 , 71 ], suggests local androgenic signaling independent of fluctuations in peripheral testosterone. The importance of SRD5A2 to prostatic development in humans and laboratory rodents is demonstrated by the small and undeveloped prostates present when a mutation in the gene prevents expression of a functional enzyme [ 14 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Letrozole treatment rapidly reduces circulating estrogen levels [4], as illustrated in Figure 1. Treatment and results from other analyses of all of these animals, including steroid levels, were previously described and indicated that letrozole treatment dramatically reduced estrogen synthesis as expected [9][10][11][12].…”
Section: Animals and Treatmentsmentioning
confidence: 60%
“…Bulbourethral glands were collected from littermate pairs of boars at the following postnatal ages: early juvenile 2 weeks (n = 2 treatment, n = 2 control), juvenile 6.5 weeks (n = 4 treatment, n = 4 control), early puberal 16 weeks (n = 6 treatment, n = 6 control), and postpuberal 40 weeks (n = 2 treatment, n = 2 control) [9][10][11][12]. Ages were chosen to represent physiological states and apparent transition points in control animals.…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…Among domestic mammals, the male pig shows the higher circulating DHEAS concentrations (13). However, SULT2A1 and SULT2B1 are poorly expressed in the boar adrenals in comparison with testes (36), and available data suggest that DHEA sulfonation occurs mainly in testicles and epididymis (36)(37)(38)(39)(40). DHEAS is undetectable in plasma of nonpregnant gilts (37) and in the adrenal of adult cycling sows (19).…”
Section: Adrenal Dhea/dheas Synthesismentioning
confidence: 99%